2021
DOI: 10.1097/wad.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Novel PSEN1 and PSEN2 Mutations Identified in Sporadic Early-onset Alzheimer Disease and Posterior Cortical Atrophy

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As it is easier to find causative mutations in FALS, whole-exome sequencing (WES) was performed in all the 16 FALS cases whose DNA samples were available. The WES was performed as the methods described previously [ 33 ]. Briefly, whole blood-derived DNA was captured to generate a sequencing library using the Agilent SureSelect Human All Exon V6 Kit (Agilent Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
“…As it is easier to find causative mutations in FALS, whole-exome sequencing (WES) was performed in all the 16 FALS cases whose DNA samples were available. The WES was performed as the methods described previously [ 33 ]. Briefly, whole blood-derived DNA was captured to generate a sequencing library using the Agilent SureSelect Human All Exon V6 Kit (Agilent Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Li et al reported another Chinese early-onset AD patient harboring the PSEN2 M239T in 2021. He presented with visuospatial and memory impairment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%